Study of some biochemical variables of liver and kidney functions of white rats under the effect of chloramphenicol - Albashir MA. Yahmed, Nasser M I Alaasswad, Ghadah F. Alajwad, Abdulhakeem A. Loiwafah, Ahmed S. Daow, Mohamed A. Bashir (Journal of Pure & Applied Sciences, 2018)
Objective: Chloramphenicol is an antibiotic for gram negative and positive bacteria, and commonly used in developing countries. It is thought to have negative effects on liver and kidneys. This study aimed to investigate the toxic effect of the drug on renal and hepatic functions of white laboratory mice. Materials and methods: 44 adult mice of both sexes were randomly divided in to four groups, each containing 11 mice. A control group was injected with only 0.9% physiological saline solution and the other three groups were injected intramuscular with drug for 10 consecutive days. The first group was injected by (25 mg / kg of mouse weight), the second (50 mg / kg of mouse weight) and the third injected (100 mg / kg of mouse weight). The concentration of urea, creatinine and total bilirubin was measured and the efficacy of liver enzymes (GGT, ALP and ALT) was assessed. Results: The concentration of urea in serum was increased by increase the amount of injected drug. The increase was statistically significant when comparing the second group and third group with the control group (P< 0.05). The results also showed that, there were no significant differences between creatinine concentrations in four studied groups (p> 0.05). A slight increase in total bilirubin was observed with increased dose of the drug. However, a high dose of the drug had a statistically significant difference compared with the blood level of the control group. The results showed a significant increase in the effectiveness of GGT in the third group compared with the control group, while no significant differences were observed for the other groups. The increase was gradual by dose concentration in the efficacy of alanine aminotransferase (ALT). This increase was statistically significant between the control group and all other groups. For alkaline phosphatase, a significant difference was observed between the control group and the second and third groups. Conclusion: The study concluded that Chloramphenicol may not have high renal toxicity but may have toxic effects on the liver function due to the metabolism of this drug.